PWE-091 Monitoring faecal occult blood test positivity in the NHS bowel cancer screening programme. (28th May 2012) - Burtonwood, C; Butler, P; Young, M; Halloran, S
Abstract : Introduction: The guaiac-based faecal occult blood test (gFOBt) used by the NHS Bowel Cancer Screening Programme relies on subjective visual assessment of colour change to determine positivity. The Southern Hub, one of five Programme Hubs in England, serves a total population of about 14.4 million people and handles about one million gFOBt kits every year. Methods: Test kit readers are tested for colour blindness and visual acuity before structured training and a period of supervision. Consistent test positivity within predefined limits is a quality measure of test kit readers and their performance is subject to weekly scrutiny. The percentage of positive test spots (six per test kit) is recorded weekly for every reader who completes >100 kits. The acceptable spot positivity range has been fixed at between 1.0% and 4.0%, based on an approximation of ±2 SDs from the mean percentage positivity for all Hub staff over a rolling 6-month time period. Results: Screening Hubs have noticed characteristic positivity patterns among readers and this reflects the subjective nature of the measurement system. The data challenge Hubs to investigate idiosyncratic test kit reading habits of staff, to modify behaviour as indicated and monitor anticipated improvements in reading performance. The screening algorithm adopted in England results in approximately 85% of screen-positive participants completing two or three test kits. While this minimises the impact of individual readers, it adds complexity to the analysis of reader positivity. Repeat kits have a higher positivity and can bias reader weekly mean positivity rates. For all readers with high weekly positivity the proportion of second and third kits read forms part of the weekly assessment. Conclusion: The Southern Hub has monitored reader positivity since August 2010 and the results are encouraging, with a reduction in reader imprecision and outliers. Initially, there was some resistance to monitoring positivity rates and the fear of being an outlier has the potential to lead staff to inappropriately modify their kit reading behaviour. New staff attend training sessions to learn about the concept of reader positivity and the interventions that may be put in place if their positivity falls outside the acceptable range. The process has now been widely accepted and the number of occasions that positivity falls outside this range per month is used as a key performance indicator. Competing interests: None declared.